Operational challenges that may affect implementation of evidence-based mobile market interventions - Christina M. Kasprzak; Anne E. Lally; Julia J. Schoonover; Deanna Gallicchio; Lindsey Haynes-Maslow; Leah N. Vermont; Alice S. Ammerman; Samina Raja; Laurene Tumiel-Berhalter; Jill N. Tirabassi; Lucia A. Leone (BMC, 2022)
Abstract Introduction Mobile produce markets are becoming an increasingly prevalent, accepted, and effective strategy for improving fruit and vegetable (F&V) access and consumption across underserved and lower-income communities. However, there is limited published research on mobile market operations. The goal of this research is to identify the challenges mobile markets face and ways to potentially mitigate those challenges. We will also discuss implications of our findings for future implementation of evidence-based food access interventions. Methods We conducted 21 semi-structured key informant (KI) interviews to assess common practices of mobile market organizations that had been operating for 2 + years. We asked KIs about their organizational structure, operations, procurement and logistics, evaluation efforts, marketing and community engagement, success and challenges. A primary qualitative analysis involved deductive coding using qualitative software. A secondary qualitative analysis identified subthemes related to common challenges and remedial practices. A deductive coding process was applied to match identified challenges to the appropriate Consolidated Framework for Implementation Research (CFIR). Results The leading challenges cited by KIs correspond to the CFIR domains of inner setting (e.g., funding and resources), outer setting (e.g., navigating regulations), and process (e.g., engaging community partnership). Practices that may mitigate challenges include maximizing ancillary services, adopting innovative volunteer and staffing structures, and formalizing agreements with community partners. Conclusion Common and persistent challenges ought to be addressed to ensure and enhance the positive public health impacts of mobile produce markets. Contextual factors, particularly organizational factors, that impact implementation should also be considered when implementing an evidence-based intervention at a mobile market. Further research is needed to determine which innovative solutions are the most effective in mitigating challenges, improving implementation, and enhancing sustainability of mobile markets.